Front Cover: In Situ Enzyme Immobilization with Oxygen‐Sensitive Luminescent Metal–Organic Frameworks to Realize "All‐in‐One" Multifunctions (Chem. Eur. J. 21/2019). Issue 21 (15th March 2019) - Xu, Yuzhi; Liu, Si‐Yang; Liu, Junling; Zhang, Li; Chen, Danping; Chen, Jun; Ma, Yingjun; Zhang, Jie‐Peng; Dai, Zong; Zou, Xiaoyong
Abstract : Metal‐organic frameworks (MOFs) for enzyme immobilization have already shown some superior characteristics; however, their devisable responsive properties have rarely been exploited. This work adopted a facilely synthesized, oxygen‐sensitive luminescent MOF, MAF‐2, for the immobilization of glucose oxidase (GOx) to give GOx@MAF‐2. The MAF‐2 scaffold played both protective and sensing functions in GOx@MAF‐2, which possessed much improved stability and was applied for glucose detection in human sera without any other additional reagents. More information can be found in the Full Paper by J.‐P. Zhang, Z. Dai, et al. on page 5463 .